Penerapan Model Laporan Keuangan Entitas Mikro Kecil Menengah Berdasarkan SAK EMKM: Sebuah Analisa Kesiapan - Ayu Amami, Cindy; Ilmiddaviq, Muhammad Bahril (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
Financial reports are not only used as a means of securing business capital, but can also be used as information for evaluating business performance. Many business owners, especially MSMEs, still lack understanding of the importance of financial reports. The Indonesian government has a plan for MSME owners to prepare financial reports to facilitate capital provision and increase global competition. SAK EMKM is an Accounting Standard for MSMEs in preparing financial reports. This study aims to gather information about the presentation of financial reports and the readiness of MSMEs in implementing the financial report model for Micro, Small, and Medium Entities based on SAK EMKM at UD. Perdana Collection, a bag manufacturer in Mojokerto, using a descriptive qualitative method. Based on the results of the study, it can be concluded that UD. Perdana Collection has not yet prepared financial reports based on SAK EMKM and is not yet ready to implement financial reports based on SAK EMKM because none of the readiness assessment indicators have been met. The obstacles faced are a lack of accounting knowledge, the absence of specialized accounting employees, and the lack of separation of business finances from personal finances.